Homeotic gene expression in the visceral mesoderm of Drosophila embryos. - Tremml, G (1989)
The visceral mesoderm adhering to the midgut constitutes an internal germ layer of the Drosophila embryo that stretches along most of the anteroposterior axis (parasegment 2-13). Most cells of the midgut visceral mesoderm express exclusively one of five homeotic genes. Three of these genes, Antennapedia, Ultrabithorax and abdominal-A are active in parasegmental domains characteristic for this germ layer as they are nonoverlapping and adjacent. The common boundaries between these domains depend on mutual regulatory interactions between the three genes. The same genes function to control gut morphogenesis. Two further homeotic genes Sex combs reduced and Abdominal-B are expressed at both ends of the midgut visceral mesoderm, although absence of their expression does not appear to affect gut morphogenesis. There are no regulatory interactions between these two and the other homeotic genes. As a rule, the anterior limit of each homeotic gene domain in the visceral mesoderm is shifted posteriorly by one parasegment compared to the ectoderm. The domains result from a set of regulatory processes that are distinct from the ones ruling in other germ layers.